DIAGNOSIS OF EMOTIONAL BURNOUT SYNDROME AMONG BANKING EMPLOYEES (Psychology Travelogs, 2023)
This article presents the results of an empirical research of the levels of emotional burnout, psychological well-being, social well-being, and the level of job satisfaction of Privatbank employees on the example of technical support managers of the Privatbank hotline.The results of our research were processed and analyzed (Sampling included 30 technical support managers of the hotline of Privatbank), the results of the empirical research were systematized, the need for measures to prevent professional burnout among bank employees was identified, general conclusions were formulated regarding the research and prospects for further development in in this direction.Burnout in the banking industry is strikingly overwhelming. Burnout is often viewed as a subprime crisis, and as such, no one ever sees it coming. Even though employees experience Burnout, they are not aware of the extent to which it would adversely affect them. Burnout is a state characterised by physical, emotional, or mental exhaustion, and when left unmanaged, can cause major breakdown among employees. And according to the World Health Organisation, Burnout is a legitimate medical condition. The main symptoms are: - lack of energy, low vitality, and loss of sharpness in thinking, decreased work engagement, difficulty in concentrating, reduced productivity, irritability, sleep difficulties, anxiety, dysphoria, recurring sickness, and absenteeism.The results obtained by us can be used in the practical activities of psychologists who work with a contingent of employees in various fields who are prone to professional burnout, and with bank employees in particular. Burnout can strike bankers since they withstand too many pressures with too little time. Due to the fact that emotional burnout syndrome has an extremely negative effect on both the personal and professional sphere of the employee's life, measures should be taken to prevent this syndrome. Prospects for further research in this direction are a detailed analysis of the features of emotional burnout among banking workers in other professional groups of Privatbank: lawyers, economists, IT specialists.
Keywords: burnout; professional burnout; emotional burnout syndrome; prevention; bank employee